Methadone Pharmacokinetics in Geriatric Critically Ill Patients Following Intramuscular and Intravenous Administration: A Pilot Stud - Beik Rassouli, Safoura; Rouini, Mohammad Reza; Najmeddin, Farhad; Gheimati, Azin; A Golabchifar, Ali; Tabib, Kimia; Ahmadi, Arezoo; Sadeghi, Kourosh; Honarmand, Hooshyar; Hadi, Ali Mohammed; Mojtahedzadeh, Mojtaba (Journal of pharmaceutical care, 2020)
Background: Methadone is used for the pain management worldwide. Its special characteristics make it a potential alternative for pain management in critically ill and geriatric patients. Due to lack of studies in this population, we aimed to compare the pharmacokinetic behavior of Methadone following intramuscular and intravenous administration in geriatric ICU patients and with previously reports in healthy volunteers. Methods: According to the limitations in ICU setting, we could include 11 patients over 65 years old, who required opioid for pain relief in this study. Patients were randomized to receive 5 mg of Methadone IM or IV injection every 8 hours for 6 days. The Methadone plasma level detected with LC-mass tandem mass spectrometry, and pharmacokinetics parameters were evaluated for each subject in both 1st and 6th days of treatment. Results: Based on our results, bioavailability of intramuscular Methadone in geriatric ICU patients was low and less than 40% of the dose was absorbed within first 12 hours. The volume of distribution of Methadone in the first day was significantly lower than the previously reported values in healthy subjects and significantly increased during these 6 days. The Methadone half-life in this population also significantly increased through this period. Conclusion: Pharmacokinetic behavior of Methadone in geriatric ICU patients is unpredictable. Reduced volume of distribution and half-life may be observed initially, following with an increase to the normal range. It seems that IM administration of Methadone in geriatric critically ill patients may not provide target analgesic Methadone serum levels.